Late Medieval Italian art and its contexts : essays in honour of Professor Joanna Cannon - Cooper, Donal; Williamson, Beth (Boydell studies in medieval art and architecture., 2022)
Former doctoral students come together to write essays in tribute to their supervisor, Joanna Cannon, whose scholarship and teaching have helped shape the historical study of thirteenth- and fourteenth-century Italian art.